Primary adrenal insufficiency - Addison's disease - Metelski, Jakub; Metelska, Aleksandra; Sereda, Dominika; Nieścior, Hubert; Szwed, Monika (Journal of Education, Health and Sport, 2022)
Introduction and purpose Addison's syndrome is defined as primary adrenal insufficiency, the symptoms of which result from hormonal deficiencies: glucocorticosteroids, mineralocorticosteroids and androgens. Currently, autoimmunity is considered the most common cause of Addison's Syndrome. Antibodies are most often directed against the enzymes 21-hydroxylase and 17-hydroxylase involved in steroidogenesis. The aim of the study is to present a typical clinical course, diagnostic path and current therapeutic options of Addison's syndrome. Description of the state of knowledge Currently, in developed countries, the number of cases is 100-140 people per million people. Initially, Addison's syndrome runs secretly. The clinical picture is closely correlated with the degree of adrenal cortex destruction. The most common symptoms include hypotonia, weight loss, weakness, salt craving, gastrointestinal disorders, and hyperpigmentation of the skin and mucous membranes. In extreme cases, adrenal crisis may develop, characterized by rapid clinical deterioration with hypotension, fever, vomiting, dehydration, and loss of consciousness. Diagnostics uses the measurement of the concentration of morning cortisol and corticotropin (ACTH) in the blood, and in doubtful situations, additionally a stimulation test using synthetic ACTH. Summary A diagnosis of Addison's syndrome requires end-of-life hormonal substitution. For this purpose, hydrocortisone or prednisone and fludrocortisone are used. In stressful situations, the doses of glucocorticoids should be adequately increased. Patients with adrenal crisis require intensive fluid resuscitation to restore intravascular volume, correct hypoglycemia and electrolyte disturbances, and administer rapidly high doses of hydrocortisone.